2017
DOI: 10.1021/acs.jafc.6b05134
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Discovery of Potential Fungicides as Succinate Ubiquinone Oxidoreductase Inhibitors

Abstract: A series of diphenyl ether-containing pyrazole-carboxamide derivatives was designed and synthesized as new succinate ubiquinone oxidoreductase (SQR) inhibitors. This highly potent molecular scaffold was developed from a moderately activie hit 3, obtained from our previous pharmacophore-linked fragment virtual screening (PFVS) method. The results of greenhouse tests indicated that some analogues showed good SQR inhibitory activity, with promising fungicidal activity against Rhizoctonia solani and Sphaerotheca f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
133
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(145 citation statements)
references
References 47 publications
6
133
0
1
Order By: Relevance
“…Furthermore, the recent studies on the structural modification of amide SDHI fungicides mainly focused on the substituents in aromatic ring and polar moiety. [7][8][9][10][11][12][13][14] Recently, several literatures reported the effect of changes in the amide bridge on fungicidal activity, such as ⊍-hydroxy and ⊍-carbonyl chiral amide ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the recent studies on the structural modification of amide SDHI fungicides mainly focused on the substituents in aromatic ring and polar moiety. [7][8][9][10][11][12][13][14] Recently, several literatures reported the effect of changes in the amide bridge on fungicidal activity, such as ⊍-hydroxy and ⊍-carbonyl chiral amide ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the inhibitory activities of cytochrome bc 1 complex and succinate dehydrogenase inhibitors have been found to be in the picomolar and nanomolar ranges, respectively. [28][29][30] To improve the screening efficiency, we further developed a new web server based on the PFVS approach, the Auto Core Fragment in silico Screening (ACFIS) server. 31 To continue work on the discovery of antiresistance AHAS inhibitors with higher potency, we carried out a PFVS with pyrimidinyl-salicylic as the pharmacophore in wild-type AHAS and P197L mutant using the ACFIS server.…”
Section: Introductionmentioning
confidence: 99%
“…An SAR study reported that the oxazolyl carbamate skeleton plays an important role in its activity profile, while a complex macrolide skeleton has little effect on it [70]. Instead of this complex and less important left chain in neopeltolide, simple biaryl moiety was inspired by other similar fungicide metominostrobin 36 , famoxadone 37 , or other biaryl ethers, as illustrated in Scheme 6 [71].…”
Section: Resultsmentioning
confidence: 99%